Numeracy Literacy Skills in the ELPSA Learning Model with the Realistic Mathematics Education Approach Viewed from Students' Mathematics Anxiety - Mutik, Rossa; Kartono; Kharisudin, Iqbal (Universitas Tidar, 2024)
This article aims to synthesize various studies related to numeracy literacy skills in the ELPSA learning model with the Realistic Mathematics Education approach, and its impact on students' mathematics anxiety. Using the Systematic Literature Review (SLR) method and meta-synthesis, this research examined how applying the ELPSA model combined with the Realistic Mathematics Education approach can improve students' numeracy skills while reducing their mathematics anxiety. The analysis found that this learning model is effective in helping students better understand mathematical concepts more openly and contextually, while supporting the enhancement of numeracy literacy through a Realistic Learning-based approach. Moreover, more positive interactions between students and the learning material help reduce anxiety in mathematics learning. The implications of this research highlight the importance of integrating the ELPSA and Realistic Mathematics Education models as a strategy that can optimize mathematics learning outcomes, create a more inclusive learning environment, and reduce students' psychological barriers.